Future landscapes of Switzerland: Risk areas for urbanisation and land abandonment. (February 2015) - Price, Bronwyn; Kienast, Felix; Seidl, Irmi; Ginzler, Christian; Verburg, Peter H.; Bolliger, Janine
Abstract: In Switzerland, the decreasing significance of agriculture has led to prominent processes of land abandonment in mountainous areas where the maintenance of open land relies on human intervention. At the same time, urbanisation in Switzerland is increasing at a rapid rate at the expense of other land use types, particularly open land agriculture. In spite of these observed trends, the extent and location of anticipated land-use changes for the coming 20 years remain unknown, as does the impact on landscape services. This research defines 5 scenarios of future land-use for Switzerland along axes of Globalisation to Regionalisation and Market-driven developments to high policy intervention. Using the Dyna-CLUE land use modelling framework we incorporate socio-economic and bio-geographical variables to model scenarios of land change for 2035. By identifying locations for key land use transitions which occur across several scenarios, we find that unless large scale policy interventions are made, large areas of the Swiss Plateau and Alpine valley bottoms face strong urbanisation and much of the mountainous pasture agriculture continues to face risk of abandonment. Highlights: We define 5 scenarios of future land-use for Switzerland to 2035. Population pressure is key driver of land use transition. Risk areas for land abandonment are widespread and not limited to mountain regions. Assertive policy intervention is needed to prevent wide-scale urbanisation.